Production of heterologous IgG antibody against Heymann nephritis antigen by injections of immune complexes - Barabas, Arpad Z (Blackwell Publishing Ltd, 2012)
Heterologous IgG antibody (ab) can be produced against Heymann nephritis (HN) antigen (ag) in rabbits by administering it in Freund's complete adjuvant. The developing abs reacted at high titre with rat kidney brush border (BB) regions of the renal proximal tubules in an indirect fluorescence ab test. A single IV injection of the heterologous ab into a susceptible strain of rat resulted in the localization of IgG ab to glomerular fixed ags, producing immune complex glomerular nephritis. The injected ab also reacted with the BB region of the renal proximal tubules. The aim of this experiment was to find out whether heterologous IgG ab against the HN ag can also be produced in recipient rabbits by injecting immune complexes (ICs) composed of a rat kidney tubular preparation [rat kidney fraction 3 (rKF3)] and donor rabbit–derived rabbit anti-rKF3 IgG ab. We found that anti-rKF3 IgG ab – against the BB region of the renal proximal tubules – could be induced in rabbits injected with ICs, and the resulting ab was able to initiate passive HN in rats. This was the first time a pathogenic IgG ab was produced against HN ag in rabbits without the use of adjuvant. Ab responses in recipient rabbits were achieved by ab information transfer. Recipient rabbits injected with the IC produced the same class of immunoglobulin with the same specificity against the target ag rKF3, as was present in the innoculum, namely rabbit anti-rKF3 IgG ab.